Formation of grain structure and its change during the superplastic deformation of samples of alloys Al-4,1 wt.% Cu-0,5 wt.% Zr, 1450 and 1460, doped with zirconium and scandium - V.P. Poyda; A.V. Poyda (Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ: fìzika.)
The article presents the results of research aimed at establishing the mechanisms of formation of ultrafine-grained structure in samples of Supral Al-4.1 wt.% Cu-0.5 wt.% Zr, 1450 and 1460 alloys, containing dispersed particles of zirconium and scandium aluminides which are effective stabilizers of the microstructure as well as at establishing the peculiarities of its change during superplastic deformation. It is established that static recrystallization plays an important role in the formation of ultrafine-grained grain structure with an average grain size d =5 μm in samples of the alloy Al-4.1 wt.% Cu-0.5 wt.% Zr. It takes place during their heating in air to the test temperature T = 773 K. Finally, the formation of the grain structure in the samples is completed in the initial stages of their superplastic flow due to the passage of continuous dynamic recrystallization. It was found that the grain structure in the working parts of the samples of the alloy Al-4.1 wt.% Cu-0.5 wt.% Zr, superplastically deformed to fracture by hundreds of percent, is ultrafine-grained ( d ≈10 μm) and equiaxed. It is established that recrystallization annealing of 1450 alloy samples does not lead to the formation of a homogeneous fine-grained structure in them. It is shown that an almost homogeneous microstructure with an average grain size d =3÷6 μm is created directly during their superplastic deformation at temperatures of 753, 763, 773, 778K and flow stresses σ = 2,0 ¸ 8,0 MPа to degrees of relative deformation εrel, amounting to 20-50%, due to the implementation of continuous dynamic recrystallization. During the subsequent stages of the superplastic flow, the average grain size increases in the working part of the samples of alloy 1450. It is shown that in the samples of alloy 1450, which were deformed to failure under the optimal conditions, the grains retain an equiaxed shape, and their average size is 10 – 15 μm. It is established that the ultrafine-grained grain structure in the working parts of samples of alloy 1460 with an average grain size d =5 μm increases during their superplastic deformation, which is carried out at temperatures in the range T = 753÷853 K and at flow voltages σ equal to 3.0÷6.0 MPa. It is shown that in samples of alloy 1460, which were deformed to failure by 1000% at Т = 823 К and s = 3,5 MPa, average grain size d ≈15 μm.